2015
DOI: 10.1021/acscatal.5b02070
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Stereoselective [2,3]-Rearrangement Reactions

Abstract: [2,3]-Sigmatropic rearrangement processes of allylic ylides or their equivalents can be applied to a variety of different substrates and generate products of wide interest/applicability to organic synthesis. This review describes the development and applications of stereoselective [2,3]-rearrangement reactions in which a substoichiometric amount of a catalyst is used in either the formation of the reactive intermediate or the [2,3]-rearrangement step itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 173 publications
0
118
0
Order By: Relevance
“…To further explore the synthetic versatility of DFHZ‐Tfs, we studied the Doyle–Kirmse reaction—a unique method for constructing C(sp 3 )−S and C−C bonds through [2,3]‐sigmatropic rearrangements . A survey of the literature revealed that Doyle–Kirmse reactions involving CHOCHN 2 and CF 2 HCHN 2 had not been explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the synthetic versatility of DFHZ‐Tfs, we studied the Doyle–Kirmse reaction—a unique method for constructing C(sp 3 )−S and C−C bonds through [2,3]‐sigmatropic rearrangements . A survey of the literature revealed that Doyle–Kirmse reactions involving CHOCHN 2 and CF 2 HCHN 2 had not been explored.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the synthetic versatility of DFHZ-Tfs, we studied the Doyle-Kirmse reaction-a unique method for constructing C(sp 3 ) À Sa nd C À Cb onds through [2,3]-sigmatropic rearrangements. [20] As urvey of the literature revealed that Doyle-Kirmse reactions involving CHOCHN 2 and CF 2 HCHN 2 had not been explored. In this context, we first evaluated the Doyle-Kirmse reaction of DFHZ-Tfs with allyl sulfide under the aqueous conditions (3 mol %F eTPPCl (TPP = meso-tetraphenylporphyrine) as the catalyst in aqueous NaOH/DCE mixture;f or details see the Supporting Information, Table S3;Scheme 3a,conditions A).…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] The power of these transformations lies in their ability to convert achiral starting materials into products with vicinal stereocenters in high enantioselectivity and diastereoselectivity. In this context, catalytic processes via metal carbenoid intermediates have been especially useful (Scheme 1A).…”
mentioning
confidence: 99%
“…Doyle-Kirmse reaction) [10] represents a powerful method for the creation of new C–C bonds, which has found application in the synthesis of various biologically active molecules. [11] This process involves a reaction between the allyl sulfide and a metallo-carbenoid species, leading to formation of a sulfur ylide which undergoes a [2,3]-sigmatropic rearrangement. [10c, 11] While several organometallic catalysts, including rhodium, [10b, 12] copper, [12a–c, 13] and cobalt [14] complexes, have proven useful for promoting this transformation, [15] the development of catalytically efficient and enantioselective variants of this reaction has proven very challenging.…”
mentioning
confidence: 99%
“…[11] This process involves a reaction between the allyl sulfide and a metallo-carbenoid species, leading to formation of a sulfur ylide which undergoes a [2,3]-sigmatropic rearrangement. [10c, 11] While several organometallic catalysts, including rhodium, [10b, 12] copper, [12a–c, 13] and cobalt [14] complexes, have proven useful for promoting this transformation, [15] the development of catalytically efficient and enantioselective variants of this reaction has proven very challenging. [11b] Here, we report the development of myoglobin-based biocatalysts capable of promoting asymmetric Doyle-Kirmse reactions with high catalytic efficiency across a broad panel of allylic and propargylic sulfide substrates and different α-diazoesters.…”
mentioning
confidence: 99%